PENERAPAN GREEN ECONOMI DALAM RANGKA PENINGKATAN PERTUMBUHAN PEMBANGUNAN YANG BERKELANJUTAN DI INDONESIA - Nurvi Oktiani (Universitas Bina Sarana Informatika, 2012)
This research describe how to implication the Green Economy for increasing going concern thegrowth development in Indonesia. The research uses library research methode.Globalization giveinfluence for building industrilization, and prosperity, while the industrilization give good and badimpact, in the phenomena in the world, in spite of industrilization and development is one of vitalcomponent, in other side it has been problem of area contamination, and if this problem hasn'tbeen finished, it would be the big matter for survival of Environtment. based on the problem, thepurposes of this research are look for and know that best solution and strategy within how toarrage and apply the planning of development and environment harmoniously and sustainable,and the one of solution is Green Economy, and the green economy is one of policy which it use forsolving the matter, there is a lot of Strategy which it can be implemented example greenrevolution, green Chemistry etc, but one of important thing, all of impact from industrilization anddevelopment can be solved by participation of stakeholderKey word : Green Economy